Generación y composición de residuos sólidos domiciliarios en Honduras durante la pandemia Covid-19 - Requena Sánchez, Norvin; Carbonel Ramos, Dalia; Romero Centeno, Rómulo (Ingeniería, 2022)
Context: Solid waste management during the Covid-19 pandemic has caused environmental effects that have not been sufficiently studied, especially in Latin American cities. This study presents a characterization of waste in Honduras during the Covid-19 lockdown, which uses a novel methodology that allows collecting information without the need for fieldwork. Method: This study was implemented in three phases (data recording, training, and data generation). All activities were carried out with the support of virtual tools such as forms and group calls. The participants received four training sessions and characterized their residues for seven days. Results: The waste generation per capita was 0,475 kg/inhab/day at the national level and 0,549 kg/inhab/day in Distrito Central [the central district]. There is an increase in the proportion of non-usable inorganic waste and a decrease in organic and recyclable waste. It is estimated that each household generates 3,7 masks nationwide and 4 masks in Distrito Central on a weekly basis. Conclusions: The per-capita generation of household waste decreased during the lockdown, which may be due to a decline in families’ purchasing power given the reduction in the economic activities. The appearance of a new residue is recorded: disposable masks and gloves.